P3-S6.10 Analysis of systemic and cutaneous immune responses helps explain the duality of immune evasion and recognition in secondary syphilis. (10th July 2011) - Cruz, A; Ramirez, L
Abstract : Background: Despite the robust adaptive immune responses associated with secondary syphilis (SS), which include the presence of high titres of anti- T pallidum (Tp) antibodies with opsonizing activity, it may take months to years for host defenses to gain control of the infection. Tp's unusual outer membrane architecture is believed to underlie this duality of immune evasion and recognition. To better understand the dynamics of immune evasion and Tp clearance in early syphilis, we studied immune responses of SS patients in peripheral blood (PB) and skin in relation to Tp burdens. Methods: 27 HIV(-) SS patients and 26 healthy controls were enrolled. Circulating monocytes, dendritic cells (DCs) and natural killer (NK) cells were characterised by flow cytometry and qRT-PCR. SS skin biopsies were analysed by immunohistochemistry (IHC) and microarray. Ex vivo opsonophagocytosis assays were performed with live Tp (Nichols) and purified human monocytes. Results: Despite the demonstrated presence of Tp in blood, circulating monocytes exhibited only mild activation by flow cytometry without detectable cytokine production by qRT-PCR. We also observed decreased numbers of circulating IFNg-producing and cytotoxic NK cells along with an emergent CD16+/CD56- NK-cell population. In contrast, skin lesions, which contained abundant Tp by IHC and PCR, contained transcripts for a variety of pro-inflammatory cytokines (IFNg, TNFa, IL1b), monocyte chemotactic factors (CCL2, CCL5 and CXCL10) and macrophage and DC surface activation markers (CD80, CD86). Transcripts for genes associated with Fc-mediated phagocytosis (FcgRI, FcgR3), endosomal TLRs (TLR7-9), and cytotoxic T cells (CD8, granzyme, perforin) also were detected in lesional skin. IHC corroborated the presence of macrophages and CD4 and CD8 T cells, but not NK cells, in the biopsies. Patient sera promoted Tp uptake and monocyte activation, although substantial proportions of Tp were capable of evading phagocytosis. Conclusions: Our results support a model in which the duality of immune evasion/recognition which occurs in SS reflects the relative burdens of Tp in skin and blood as well the presence of Tp populations with differential capacity for binding opsonic antibodies. Macrophage activation due to opsonophagocytosis of a subpopulation of Tp drives the recruitment to skin of immune cells that slowly clear infection. Results also suggest that cytotoxic cellular responses may contribute to elimination of Tp.